Aspek Keadilan dalam Pengupahan pada UMKM di Indonesia - Lidia Febrianti; Puti Mayang Seruni; Nadia Aulia (Jurnal Hukum Lex Generalis, 2026)
MSMEs contribute 60.5% of Indonesia's total GDP, with a national workforce absorption rate of 96.9% in 2022. This makes MSMEs a critical engine for national economic progress. The government's enthusiasm for supporting MSMEs is demonstrated, among other things, through special wage regulations for MSMEs, which are lower than the minimum wage, as outlined in Government Regulation Number 36 of 2021 concerning Wages. The policy is beneficial for MSMEs with limited capital because they are exempt from the usual minimum wage obligations. However, this wage is a tragedy for MSME workers, as it is low and insufficient to meet a decent standard of living. This research examines in depth whether the wage policy for MSME workers has met the aspect of justice in industrial relations, considering that Article 27, paragraph 2 of the 1945 Constitution firmly states that "every citizen has the right to work and a decent living for humanity." The research results show that the aspect of justice in wages must include aspects of distributive justice, where equal work must be paid equally, substantive justice, where the nominal wage received must be appropriate, procedural justice, where the wage determination process must be fair and transparent and relational justice, where the social status of workers does not become an obstacle in determining a decent wage. MSMEs are exempted from minimum wage obligations to maintain their sustainability due to limited capital and competitiveness. However, for workers, this policy results in the aspects of substantive, distributive, procedural and relational justice in wages not being fully met. A gradual wage policy and work flexibility are needed for MSMEs so that the economic interests of workers and the sustainability of MSMEs can be balanced.